Efficacy of hyaluronidase and dexamethasone intralesional injections in the management of oral submucous fibrosis (Journal of Pharmaceutical Negative Results, 2022)
Objective: To evaluate the efficacy of intralesional injections of dexamethasone and hyaluronidase in the treatment of oral submucous fibrosis (OSMF).Materials and Methods: The present study included 180 patients with OSMF who were divided into four groups and 45 healthy individuals who were included in the control group. The OSMF subjects were injected with hyaluronidase 1,500 IU mixed in 1.5 ml of dexamethasone and 0.5 ml of lignocaine HCL intralesionally twice a week for one month along with a basic physiotherapy regimen consisting of mouth exercises two times daily. Individuals in the control group were administered placebo capsules. Treatment was carried out for 4 weeks, the burning sensation and mouth opening were evaluated before and after treatment.Results: A significant improvement in the mouth opening and reduction in burning sensation was noted in mild to moderate cases of OSMF after treatment.Conclusion: In this study, intralesional injection of hyaluronidase with dexamethasone is showed to be an effective method to manage the signs and symptoms in mild to moderate cases of OSMF